The trait-specific collection of large-seeded sunflower at VIR: ba source for breeding cultivars and hybrids - V. A. Gavrilova; L. G. Makarova; T. G. Stupnikova; N. V. Alpatieva; E. B. Kusnetsova; I. N. Anisimova (Труды по прикладной ботанике, генетике и селекции)
Background. In recent years, an increase has been observed in the share of sunflower seeds in the confectionery and food industries. There are 30 cultivars and only 3 hybrids for confectionery use among 839 zoned sunflower cultivars and hybrids listed in the State Register for Selection Achievements Admitted for Usage in 2023. Thus, the development of source material for breeding large-seeded cultivars and hybrids remains a relevant task.Materials and methods. The studied material included 90 accessions selected for their large seed size from VIR’s sunflower collection. The following characters were assessed: 1000 seed weight, days from sprouting to maturation, plant height, head diameter, cypsela color and size, and resistance to downy mildew. DNA markers were used to identify accessions with the Rf1 gene and CMS.Results. Accessions k-2818 (Primorsky Territory), k-3633, k-3748, k-3782 (China), and k-3578 (Ukraine) were the best in 1000 seed weight. Russian cvs. ‘Alekseyevsky Krupnoplodny 2’ (k-3552), ‘Gyar-Gyar’ (k-1589), ‘SPK’ (k-3426), and ‘Lakomka’ (k-3526) confirmed their large seed size. The sterile type of cytoplasm was identified in 12 accessions. Fourteen accessions with fertile cytoplasm had diagnostic markers of the nuclear Rf1 gene.Conclusion. The large-seeded cultivars developed at VNIIMK, ‘SPK’, ‘Lakomka’, and k-3782 from China were the best not only in their large seed size but also in downy mildew resistance. As a result of long-term studies, a trait-specific collection was established for the large seed size trait. It included 90 accessions that can be used in the development of confectionery cultivars. Large-seeded sunflower accessions carrying the Rf1 gene were identified. Some of them became the ancestors of donor lines for both pollen fertility restoration genes and large seed size.